Poročevalska sklicevalnost v agencijskih besedilih - Laban, Vesna (Družboslovne razprave, 2007)
The authors discuss how the Slovenian Press Agency (STA) quotes or summarises the opinions of its sources. Using the linguo-stylistic method, they analyse the linguistic means of reference in the STA's reports. The analysis reveals the use of 71 verbs for saying, thinking and perceiving which can be explained as a result of the journalists' attempt to write livelier texts and to avoid repetition. The use of direct speech is surprisingly rare; journalists mostly summarise the news sources' statements, referring to the reports of foreign news agencies and media organisations which lead to double or even triple references. There is also some inconsistency as to indicating the borders between the author's part of the text and the news source's opinion. The exaggerated use of syntax structure, which expresses unreliability, can be ascribed to the journalists' excessive concern to pass on the quotes objectively.
Keywords: Journalism; Novinarstvo; News agencies; Tiskovne agencije; Reporters and reporting; Poročevalci in poročanje; Besedila; Besedilo; Texts; Analiza jezika; Language analysis; poročevalstvo; viri informacij; analiza besedil; sklicevalnost; Slovenska tiskovna agencija